Early Childhood Caries: Scenario in Nepal - Sundas, Sunanda (Journal of Nepalese Association of Pediatric Dentistry, 2021)
Early childhood caries (ECC) is a virulent form of dental caries present in primary dentition and is the most common infection related disease in young children worldwide.1 It’s been on the rise in many countries, and has become a significant health problem especially in socially disadvantaged populations. ECC does not only affect teeth but it also leads to other health consequences like pain, infection, altered eating habits, sleep disturbances, altered childhood development and psychological outcomes